2019
DOI: 10.3892/etm.2019.7524
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential therapeutic target genes in mouse mesangial cells associated with diabetic nephropathy using bioinformatics analysis

Abstract: The aim of the present study was to identify genes under the effect of transforming growth factor-β (TGF-β1), high glucose (HG) and glucosamine (GlcN) in MES-13 mesangial cells and elucidate the molecular mechanisms of diabetic nephropathy (DN). The gene expression datasets GSE2557 and GSE2558 were downloaded from the Gene Expression Omnibus database. Differentially expressed genes (DEGs) were independently screened using the GEO2R online tool. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…( 42 ) indicated that CFH-associated types of mesangial proliferative glomerulonephritis were seen in end-stage kidney disease caused by hypertension or glomerulosclerosis, and fosinopril with CFH demonstrated preferred binding activity. Thus, CFH might be a target for the treatment of mesangial cells associated with DKD ( 43 ). Further results of GO and KEGG indicated that the gene is enriched in peroxisome, focal adhesion and lysine degradation pathways.…”
Section: Discussionmentioning
confidence: 99%
“…( 42 ) indicated that CFH-associated types of mesangial proliferative glomerulonephritis were seen in end-stage kidney disease caused by hypertension or glomerulosclerosis, and fosinopril with CFH demonstrated preferred binding activity. Thus, CFH might be a target for the treatment of mesangial cells associated with DKD ( 43 ). Further results of GO and KEGG indicated that the gene is enriched in peroxisome, focal adhesion and lysine degradation pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Among these core genes, some have been shown to play an important role in the pathogenesis of DN, C3 ( 52 , 53 ), ALB ( 54 56 ), EGF ( 57 ), EGR1 ( 58 61 ), COL1A2 ( 62 ), FN1 ( 63 , 64 ), CD44 ( 65 , 66 ), FOS ( 67 ), PLG ( 68 , 69 ), and DUSP1 ( 70 ). It is well-known that inflammation and fibrosis play an important role in the pathogenesis of the DN glomerulus ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…As described before, some of those factors can recruit and active immune cells ( 124 ), and those active immune cells will damage glomerular cells. Some of these factors even can damage glomerular cells directly, such as TGF-β ( 125 ), TNF-α ( 126 ), ILs ( 127 ), and FN1 ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reanalyzing available public data can provide valuable clues for new research. To date, many studies have screened numerous Differentially Expressed Genes (DEGs) involved in DN [26][27][28][29][30][31]. However, the heterogeneity of experimental samples in independent studies and the application of different detection platforms and different processing methods can lead to inconsistent results.The Robust Rank Aggreg (RRA) method is suitable for comparing several sequenced gene lists based on the assumption that each gene in each dataset is randomly arranged [32].…”
Section: Introductionmentioning
confidence: 99%